2023
DOI: 10.3389/fphar.2023.1173893
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early heparin therapy on outcomes in critically ill patients with sepsis-induced coagulopathy

Abstract: Background: This study aimed to investigate whether early unfractionated heparin (UFH) administration provides a survival advantage for patients with sepsis-induced coagulopathy (SIC).Methods: Patients hospitalized with sepsis-induced coagulopathy from the Medical Information Mart for Intensive Care (MIMIC)-IV database were identified. Patients were divided into two groups, who received unfractionated heparin (UFH) subcutaneously within 24 h after intensive care unit (ICU) admission, and the control group, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As administration heparin is time-dependence variable, so we employed MSCM model to adjust additional time-dependent interventions ( de Keyser et al, 2014 ; Karim et al, 2014 ; Huang et al, 2023 ). The MSCM further reinforces the efficacy of heparin in reducing ICU mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As administration heparin is time-dependence variable, so we employed MSCM model to adjust additional time-dependent interventions ( de Keyser et al, 2014 ; Karim et al, 2014 ; Huang et al, 2023 ). The MSCM further reinforces the efficacy of heparin in reducing ICU mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The present study adopted propensity score matching (PSM) to interpret the basic differences in whether the patient received heparin treatment ( Huang et al, 2023 ). During PSM analysis, prophylactic heparin was administered to the heparin group 24 h post-ICU admission.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-inflammatory effect of UFH is superior to that of NAH; however, UFH increases the risk of bleeding. A retrospective study of 3377 patients with SIC found that UFH (6250–13,750 IU/d) reduced the risk of death in patients with a SIC score of 4 points; however, UFH increased the risk of bleeding in clinical trials [ 73 , 95 , 96 ].…”
Section: Polysaccharides and Other Macromoleculesmentioning
confidence: 99%
“…Many studies have confirmed the therapeutic effects of heparin in sepsis, including the regulation of inflammatory reactions by antagonizing histones ( Wildhagen et al, 2014 ), inhibiting the generation of inflammatory factors ( Harada et al, 2006 ), immune regulation, and vascular protection ( Eggimann et al, 2003 ). Study by Huang and colleagues revealed that heparin administration was also associated with decreased ICU mortality in patients with an SIC score of 4 (HR 0.63, 95% CI 0.45-0.89) ( Huang et al, 2023 ). Whether heparin therapy is associated with reduced mortality in SAKI patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%